2020
DOI: 10.1134/s0006297920120160
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic ROS Signaling: To Immunity and Beyond

Abstract: Metabolism is a critical determinant of immune cell functionality. Immunometabolism, by definition, is a multidisciplinary area of immunology research that integrates the knowledge of energy transduction mechanisms and biochemical pathways. An important concept in the field is metabolic switch, a transition of immune cells upon activation to preferential utilization of select catabolic pathways for their energy needs. Mitochondria are not inert in this process and contribute to the metabolic adaptation by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 164 publications
(229 reference statements)
0
12
0
3
Order By: Relevance
“…This probe relies on two cellular catalytic activities that are prerequisite for its reactivity with hydrogen peroxide. Some clinical studies also demonstrated the bactericidal effects of ROS in clinical trials of wounds and in the reduction of biofilm during respiratory infections, but the story is far from over [92,[94][95][96]. It will be interesting to develop future ROS-based strategies as clinical therapies for microbial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This probe relies on two cellular catalytic activities that are prerequisite for its reactivity with hydrogen peroxide. Some clinical studies also demonstrated the bactericidal effects of ROS in clinical trials of wounds and in the reduction of biofilm during respiratory infections, but the story is far from over [92,[94][95][96]. It will be interesting to develop future ROS-based strategies as clinical therapies for microbial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic ROS production is involved in several essential signaling functions targeting prokaryote and eukaryote cells. ROS remain a key signaling molecules in redox homeostasis, which regulates cell growth, cell death (necrosis and apoptosis), survival, and mitochondrial metabolism [96]. Mitochondria-derived ROS are involved in the activation of AMP protein kinases, which are implicated in several cancer signaling pathways [97].…”
Section: Implications Of Ros In Microbial Therapeutic Clinical Trialsmentioning
confidence: 99%
“…Under normal conditions, 2% of electrons are diverted to reduce molecular oxygen to produce a superoxide [ 42 ]. Physiologically, ROS has been shown to regulate various crucial cellular processes, such as cellular differentiation [ 45 , 46 ], autophagy [ 47 , 48 ], metabolic adaptation [ 49 , 50 ] and immune cell activation [ 50 , 51 , 52 ]. Pathologically, ROS has often been shown to cause harm to cells, which are described as follow.…”
Section: Mitochondria Biologymentioning
confidence: 99%
“…МтАФК принимают участие во многих клеточных процессах, в том числе в клеточном цикле, авто-и митофагии, биогенезе митохондрий, а также в регуляции функционирования различных белков: ATF4, NF-kB, митоген-активируемых киназ, внеклеточных сигнал-регулируемых киназ, c-Jun N-терминальных киназ, тирозинфосфатазы и др. [13][14][15]. Кроме регуляторной роли мтАФК выполняют проапоптотические функции, а также участвуют в других, повреждающих клетку, активностях, которые индуцируются нарушением функционирования митохондрий, и могут возникать при различных патологических состояниях [13].…”
unclassified
“…[13][14][15]. Кроме регуляторной роли мтАФК выполняют проапоптотические функции, а также участвуют в других, повреждающих клетку, активностях, которые индуцируются нарушением функционирования митохондрий, и могут возникать при различных патологических состояниях [13]. Повышение уровня мтАФК может инициировать процессы, влияющие на функцию и целостность митохондрий [6].…”
unclassified